Act of Mar. 15, 1852, ch. 206, 1852 Miss. Laws p. 328 - (:unkn) unknown (General Publisher, 1852)
Prohibited issuing licenses to "negroes" to carry and use firearms.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES